Technology Blueprint of AllFit Apps / Muhammad Fikry Kamarulzaman - Kamarulzaman, Muhammad Fikry (2020)
Technology had accompanied human in completing many task and improving human lifestyle by minimizing daily hustle for needs and wants. Nowadays, every individual possessed smartphone despite their age and gender. Age of Apps has rise rapidly as market platform for many establish company out there to increase their revenue. There are verity online shopping apps that available to be download from Apps Store by smartphone user. FikryDevelop Sdn. Bhd. is a company that main business is managing and storing goods in warehouse with objective to compliment variety human lifestyle. To satisfy biggest human wants which is shopping for branded and stylish outfit from head to toes for many kinds of occasion. My company introducing a new online shopping platform that only offering items from branded company, which is AllFit Apps. The aim of AllFit Apps is to offer less hustler to branded item lover with guaranteed trusted seller and accurate size measurement as if the user being treat as a VIP customer in their favourite store. AllFit Apps offering a size comparison base on our collected data base from all branded outfit to help the user making decision to select the perfect size for the item they wanting to purchase. This is to deliver the aesthetic they desire when wearing the item as if they try the item in the store fitting room itself and look pleasant to the eyes when wearing the item. Besides that, the company offering special care for their purchases item by safely delivering their item to their doorstep with our own courier or by few selective couriers to guarantee their branded item safety. Every item will come with AllFit metal QR code keychain (item certificate) that showing prove that the item is legit and approve by their favourite branded store. This QR code can be scan by the user through the AllFit Apps and it provided the user with their purchased item details.